Pig farmers knowledge enhanced through Pig Smart extension platform in Uganda - Ouma, Emily A.; Mugabi, David; Ssimbwa, David; Kugonza, Donald, R.; Hasahya, Emmanuel; Sserwadda, Joseph; Businge, Martha; Kawuma, Peter; Oba, Peter; Ahumuza, Ronnie; Nsadha, Zachary (International Livestock Research Institute, 2024)
SAPLING Uganda team together with its partners rolled out a PigSmart extension intervention in September – October 2024 to members of pig farmer groups in Mpigi, Masaka, Mukono and Wakiso districts and reached about 1,254 farmers from 55 farmer groups (Oba et al., 2024). The objective was to empower selected farmer groups with skills and knowledge on various aspects of pig production, delivered through audio skit messages in Luganda. The PigSmart extension platform delivers extension messages to pig farmers. It covers integrated content that is delivered to pig farmers based on the stage of growth of the pigs. The messages include best practices in feeding, herd health management, breeding and genetics, manure management and heat stress management (Ouma et al, 2024). A brochure on the integrated content was developed and disseminated to pig farmers in addition to the audio skits. A herd health manual by Nsadha and Dione (2020), was used to enhance learning focused on herd health. The messages can be used by extension agents to train farmers on best practices in pig production. An endline survey was conducted in November 2024 to assess the outcomes from the intervention using a ‘with’ and ‘without’ approach by comparing outcomes for farmers from farmer groups exposed to the PigSmart intervention with a control group of those not exposed. Farmer groups exposed to PigSmart intervention were classified as the treatment group while those not exposed were the control group. Proportionate random sampling was used to draw a sub-sample of 17 treatment farmer groups and 11 control farmer groups to be considered in the survey. A total sample size of 345 farmers was drawn from the total group membership of the 28 farmer groups. Results show improved knowledge of farmers through the PigSmart extension messaging and application of the innovation and best practices by the farmers reached through PigSmart compared to the control groups.